Excreta Deposition on Grassland Patches. I. Forage Harvested, Nutritive Value, and Nitrogen Recovery. Issue 2 (1st March 2013) - White‐Leech, Renee; Liu, Kesi; Sollenberger, Lynn E.; Woodard, Kenneth R.; Interrante, Sindy M.
ABSTRACT: Livestock excreta deposition in grazed grassland is nonuniform and concentrated around shade, water, and supplement feeding locations. The consequences of repeated dung or urine deposition to grassland patches have not been well quantified in terms of effects on forage dry matter harvested (DMH), forage nutritive value, and nutrient recovery. These responses were measured on 'Pensacola' bahiagrass ( Paspalum notatum Flüggé) swards treated with two excreta types (dung and urine) from two excreta source pastures (the Average and High management intensities based on N fertilizer and stocking rates) applied at four frequencies (0, 1, 2, 3 yr − 1 ) during 2 yr. Responses were measured within a circular quadrat of radius 45 cm whose center was the midpoint of the excreta deposit. Forage DMH decreased linearly from 3040 to 2800 kg ha − 1 with increasing dung application frequency and increased from 3040 to 4820 kg ha − 1 as urine application frequency increased. Forage nutritive value did not differ among dung application frequencies but generally increased with urine application frequency. Nitrogen recovery relative to an untreated control was negative for dung, positive for urine, and decreased with increasing urine application frequency. Forage DMH was suppressed by dung, but urine increased forage DMH, nutritive value, and nutrient removal. Decreasing nutrient recovery with increasing excreta application frequency supports use of grazing strategies that increase uniformity of deposition.